Mitophagy in the aging nervous system - Rappe, Anna; McWilliams, Thomas G. (Frontiers in Cell and Developmental Biology, 2022)
Aging is characterised by the progressive accumulation of cellular dysfunction, stress, and inflammation. A large body of evidence implicates mitochondrial dysfunction as a cause or consequence of age-related diseases including metabolic disorders, neuropathies, various forms of cancer and neurodegenerative diseases. Because neurons and have high metabolic demands and cannot divide, they are especially vulnerable to mitochondrial dysfunction. The selective autophagy of mitochondria (mitophagy) neutralises mitochondrial dysfunction, providing a cellular quality control strategy and the ability to adapt and sustain metabolic homeostasis. Although extensively characterised in cultured cells and short-lived model organisms, our understanding of physiological mitophagy in mammalian aging is extremely limited. Recent studies of reporter mice have revealed variegated vistas of steady-state mitochondrial destruction across different tissues. The recent finding of families with congenital autophagy deficiency provokes further intrigue into the degradative mechanisms that sustain neural integrity. These new dimensions have considerable implications for targeting mitophagy and other degradative pathways in age-related disease.